A quest for the mechanism regulating global planar cell polarity of tissues - Wu, Jun (2009)
Most epithelial cells, besides their ubiquitous apical–basal polarity, are polarized within the plane of the epithelium, which is called planar cell polarity (PCP). Using Drosophila as a model, meaningful progress has been made in the identification of key PCP factors and the dissection of their intracellular molecular interactions. The long-range, global aspects of coordinated polarization and the overlying regulatory mechanisms that create the initial polarity direction have, however, remained elusive. Several recent publications have outlined potential mechanisms of how the global regulation of PCP might be controlled and how the distinct core factor groups might interact via frizzled, Van Gogh or flamingo. This review focuses on these exciting features and attempts to provide an integrated picture of these recent and novel insights.